A human protein with homology to Saccharomyces cerevisiae SNF5 interacts with the potential helicase hbrm. - Muchardt, C (1995)
In yeast, the SNF/SWI complex is involved in transcriptional activation of several inducible promoters, possibly by causing a local modification of the chromatin structure. Recently, two human homologues of the SNF2/SWI2 protein have been isolated, hbrm and BRG-1. In addition, a complex containing one of the SNF2/SWI2 homologues and having an in vitro activity similar to the yeast complex has been partially purified from HeLa cells. Here we describe the characterization of a cDNA encoding a human nuclear protein containing a large domain of homology with SNF5, another member of the yeast SNF/SWI complex. This protein can be co-immunoprecipitated with hbrm and the interaction between the two proteins is dependent on the region conserved between the human and the yeast SNF5. These findings suggest that the cDNA we have cloned encodes one of the members of the human SNF/SWI complex.